Penggunaan Media Puzzle Konstruksi Terhadap Hasil Belajar Kognitif Siswa SDN Kemangsen II Krian - Eka Wahyu Hidayati (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2018)
Learning is a complex process and it can occur due to the interaction between man and his environment, his teachers, his friends and even the most important and the man who became the first school of every human being is mimic their parents. A puzzle game is entertaining game and can be enjoyed by children and adults by concentrating and using his thought power optimally in a way to understand and grasp the dimensions of the puzzle in order to complete this game. This study uses a quantitative research design which is the type of research that used is quantitative experimental approaches with One Group Pretest-Postest Design, which is a type of research that provides design pretest before and after being treated. Of the two questions researchers can be found the following reply. The First, there is influence of using puzzle media construction of the cognitive achievement of students in Civics subject which to understand the freedom to organize the fifth grade at SDN Kemangsen II, it’s proved by t table for a 5% error with db = N-1 = 27 was 2.05. Because of (t count > t table) is 20.44 < 2.060. The Second, the amount of influence the media construction puzzle of cognitive achievement students in the subjects of Civics in understands the freedom to organize the fifth grade at SDN Kemangsen II in the academic year 2014/2015 amounted to 40.7%.